Composite negative electrode material, preparation method, negative electrode plate and sodium ion battery
Through the composite negative electrode material of hard carbon and titanium-based materials, through ball mill mixing and heat treatment, the safety hazards of sodium metal precipitation in sodium ion batteries and the problems of poor high-rate performance are solved, achieving higher sodium storage potential and battery safety sex.
Patent Information
- Application Number
- CN202411150566.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-10
AI Technical Summary
The low sodium storage potential of hard carbon, the negative electrode material of existing sodium ion battery, causes sodium metal to be easily precipitated during charging and discharging, poses safety risks, and has poor performance in high-magnification application scenarios.
The composite negative electrode material of hard carbon and titanium-based materials is used to bond the two through ball mill mixing and heat treatment, which increases the sodium storage potential, prevents the precipitation of sodium metal and improves the rate performance.
It effectively improves the sodium storage potential of composite negative electrode materials, prevents sodium metal precipitation and battery short circuit, enhances battery safety and rate performance, and is suitable for high-speed application scenarios.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite negative electrode material, a preparation method, a negative electrode sheet and a sodium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in energy storage fields such as portable electronic products and electric vehicles due to their high energy density and high energy conversion efficiency. However, with the development of large-scale energy storage equipment such as new energy vehicles, lithium resources are difficult to meet the widespread use of lithium-ion batteries, resulting in an increase in the cost of lithium-ion batteries year by year, limiting their development in the field of energy storage. Sodium and lithium have similar chemical properties. In recent years, the development and research of sodium-ion batteries has gradually increased, and sodium-ion batteries are also seen as the best alternative to lithium-ion batteries in the future.
[0003] Among them, hard carbon is widely used as anode material for sodium-ion batteries, but the low sodium storage potential of hard carbon easily leads to the precipitation of metallic sodium during the charge and discharge process, resulting in poor safety. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the present application provides a composite negative electrode material, a preparation method, a negative electrode sheet and a sodium ion battery, and the technical solution is as follows: On the one hand, the present application provides a composite negative electrode material, including hard carbon and a titanium-based material, wherein the hard carbon and the titanium-based material are bonded, and the composite negative electrode material is obtained by ball milling, mixing, heat treating and cooling the hard carbon and the titanium-based material.
[0005] Furthermore, the titanium-based material includes TiO2, NaTiO2, Na2Ti2O5, Na2Ti3O7, Na4Ti5O 12 、Na2Ti6O 13 At least one of .
[0006] Furthermore, the mass ratio between the titanium-based material and the hard carbon is 0.12:1 to 20:1.
[0007] Furthermore, the sodium storage potential of the titanium-based material is 0.25V to 0.35V.
[0008] Furthermore, the sodium storage potential of the composite negative electrode material is 0.1V to 0.2V.
[0009] On the other hand, the present application also provides a method for preparing a composite negative electrode material, comprising: The hard carbon and the titanium-based material are ball-milled and mixed to obtain a mixed dry material; The mixed dry material is heat treated and cooled to obtain the composite negative electrode material.
[0010] Furthermore, during the ball milling mixing process, the ball milling speed is 200 r / min to 1000 r / min, and the ball milling time is 0.5 h to 12 h.
[0011] Furthermore, the heat treatment satisfies at least one of the following characteristics: During the heat treatment, the temperature is 300°C to 500°C, the time is 2h to 8h, and the heating rate is 1°C / min to 5°C / min; The atmosphere of the heat treatment includes at least one of argon, nitrogen, hydrogen and air.
[0012] On the other hand, the present application also provides a negative electrode sheet, comprising the composite negative electrode material as described in any one of the above items, or comprising a composite negative electrode material prepared by the preparation method of the composite negative electrode material as described in any one of the above items.
[0013] On the other hand, the present application also provides a sodium ion battery, comprising the composite negative electrode material as described in any of the above items, or comprising a composite negative electrode material prepared by the preparation method of the composite negative electrode material as described in any of the above items, or comprising the negative electrode sheet as described above.
[0014] Implementing this application has the following beneficial effects: In the composite negative electrode material of the present application, hard carbon and titanium-based materials are mixed and bonded by heat treatment. Compared with the existing hard carbon negative electrode, the sodium storage potential of the composite negative electrode material can be effectively improved. In the sodium ion battery having the composite negative electrode material, the sodium storage potential of the composite negative electrode material is relative to the potential of sodium metal. The higher the sodium storage potential, the less likely it is for sodium metal to precipitate. During the charge and discharge process of the sodium ion battery having the composite negative electrode material, the precipitation of sodium metal to produce sodium dendrites and then cause a short circuit of the battery can be effectively prevented, thereby greatly improving the battery safety. At the same time, it can also be beneficial to improve the rate performance and cycle performance of the composite negative electrode material and the sodium ion battery at different charge and discharge rates. In addition, as the rate increases, that is, as the charge and discharge rate increases, the battery polarization will increase, resulting in a further decrease in the sodium storage potential and making it easier for sodium metal to precipitate. The sodium storage potential of the composite negative electrode material has been effectively improved, so that the composite negative electrode material can be suitable for high-rate sodium ion batteries, thereby improving the battery safety in high-rate application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the embodiments, wherein the same components are represented by the same reference numerals. Obviously, the drawings described below are only some embodiments of the present application, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 A graph showing the first charge and discharge curves of multiple composite negative electrode materials provided in the embodiments of the present application; Figure 2 The first charge and discharge curves of the composite negative electrode material provided in Example 1 of the present application and the negative electrode material in Comparative Examples 1-2; Figure 3 The rate performance diagram of the composite negative electrode material provided in some embodiments of the present application and the negative electrode material in Comparative Examples 1-2; Figure 4 Cycling performance diagrams of the composite negative electrode materials provided in some embodiments of the present application and the negative electrode materials in Comparative Examples 1-2. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments, and therefore cannot be understood as limiting the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0018] It should be noted that in the description of the present application, for the following defined terms, unless a different definition is given in the claims or elsewhere in this specification, these definitions should be applied. All numerical values, whether or not explicitly indicated, are defined herein as being modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art would consider to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0019] It should be noted that the terms "first", "second", etc. in the specification, claims and drawings of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the objects used in this way can be interchanged where appropriate, so that the embodiments of the present application can be implemented in a sequence other than the following diagrams or the following descriptions. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, the process, method, system, product comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, or products.
[0020] The negative electrode of existing sodium ion batteries often uses hard carbon, but the sodium storage potential of hard carbon is relatively low, about 0.1V, which makes it very easy for sodium metal to precipitate during the charge and discharge process of the sodium ion battery with the hard carbon negative electrode, causing safety problems; Based on the above problems, an embodiment of the present application provides a composite negative electrode material, including hard carbon and a titanium-based material. In the composite negative electrode material, the hard carbon and the titanium-based material are bonded, and the titanium-based material has a higher sodium insertion potential (i.e., sodium storage potential). The bonding between the hard carbon and the titanium-based material is tightly bonded, which can effectively improve the sodium storage potential of the hard carbon and the composite negative electrode material. The composite negative electrode material is applied to sodium ion batteries. The sodium storage potential of the composite negative electrode material is relative to the potential of sodium metal. If the sodium storage potential is 0V, it means that sodium metal is completely precipitated. The closer the sodium storage potential is to 0V, the higher the sodium storage potential is. The more likely sodium metal precipitation occurs, especially in application scenarios with high charge and discharge rates, and in electronic devices with high power requirements. As the rate (fast charge and discharge rate in a short period of time) increases, the battery polarization will increase, resulting in a further decrease in the sodium storage potential and making it easier for sodium metal to precipitate. The sodium storage potential of the composite negative electrode material has been effectively improved, which can effectively prevent the precipitation of metallic sodium to form sodium dendrites during the charge and discharge process, thereby preventing the battery from short-circuiting, greatly improving the battery safety, and at the same time, it is beneficial to improve the rate performance and cycle performance of the composite negative electrode material and sodium ion battery; it can also make the composite negative electrode material suitable for high-rate sodium ion batteries, improving the battery safety of the composite negative electrode material and sodium ion battery in high-rate application scenarios.
[0021] Among them, the composite negative electrode material is obtained by ball milling, mixing, heat treating and cooling hard carbon and titanium-based materials. After the hard carbon and titanium-based materials are blended, microscopic bonding between the hard carbon and titanium-based materials is promoted by heat treatment to achieve bonding of the hard carbon and titanium-based materials in the final composite negative electrode material. The hard carbon and titanium-based materials are bonded by van der Waals forces, which can greatly enhance the adsorption force between the hard carbon and titanium-based materials, enhance the bonding tightness between the hard carbon and titanium-based materials, and further help to enhance the sodium storage potential of the hard carbon, so that the sodium storage potential of the composite negative electrode material is effectively enhanced relative to the hard carbon negative electrode.
[0022] Specifically, titanium-based materials include TiO2, NaTiO2, Na2Ti2O5, Na2Ti3O7, Na4Ti5O 12 、Na2Ti6O 13At least one of the titanium-based materials has a relatively high sodium insertion potential. For example, the sodium insertion potential of sodium titanate Na2Ti3O7 is about 0.3V. Introducing titanium-based materials into hard carbon can effectively regulate the sodium storage potential of hard carbon. After the two are blended and bonded, the sodium storage potential of the composite negative electrode material can be effectively improved. In a sodium ion battery having the composite negative electrode material, the precipitation of metallic sodium and the formation of sodium dendrites during charging and discharging can be effectively prevented, and the battery short circuit can be further avoided, which greatly improves the safety of the composite negative electrode material and the sodium ion battery having the composite negative electrode material. In addition, the raw materials of the titanium-based material are abundant and non-toxic, which is conducive to further improving the safety of the composite negative electrode material and reducing costs.
[0023] In some preferred embodiments, the titanium-based material includes NaTiO2, Na2Ti2O5, Na2Ti3O7, Na4Ti5O 12 、Na2Ti6O 13 At least one of the titanium-based materials is a sodium titanate with unsaturated bonds, which is easier to form microscopic bonds with hard carbon during the preparation process, thereby improving the bonding tightness between the hard carbon and the titanium-based material in the prepared composite negative electrode material, which is beneficial to improving the rate performance and cycle performance of the composite negative electrode material, and improving the structural stability of the composite negative electrode material, further improving the durability and safety of the composite negative electrode material, as well as the negative electrode sheet and sodium ion battery having the composite negative electrode material.
[0024] Specifically, the sodium storage potential of the titanium-based material is 0.25V~0.35V; it can be understood that the sodium storage potential of the titanium-based material can be any point value in the range of 0.25V~0.35V; illustratively, the sodium storage potential of the titanium-based material can be 0.25V, 0.27V, 0.28V, 0.29V, 0.30V, 0.32V, 0.33V, 0.35V, etc.; the sodium storage potential of the titanium-based material is relatively high, while the sodium storage potential of hard carbon is about 0.1V. The titanium-based material is mixed and bonded with the hard carbon, which can greatly improve the sodium storage potential of the composite negative electrode material compared to the hard carbon negative electrode, reduce the risk of metallic sodium precipitation during the charge and discharge process of the composite negative electrode material in the sodium ion battery, greatly improve the stability and safety of the sodium ion battery, and can also improve the rate performance and cycle performance of the sodium ion battery with the composite negative electrode material to a certain extent; in some preferred embodiments, the sodium storage potential of the titanium-based material is 0.28V~0.32V.
[0025] Specifically, the particle size of the hard carbon is 5μm to 9μm; it can be understood that the particle size of the hard carbon can be any point value between 5μm and 9μm; illustratively, the particle size of the hard carbon can be 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 8μm, 9μm, etc.; within this hard carbon particle size range, it can be evenly mixed with the titanium-based material and stably produce microscopic bonding, thereby improving the bonding tightness between the hard carbon and the titanium-based material, which is beneficial to the synergistic improvement of the sodium storage potential, rate performance and cycle performance of the composite negative electrode material; in some preferred embodiments, the particle size of the hard carbon is 6μm to 9μm.
[0026] Specifically, the mass ratio between the titanium-based material and the hard carbon is 0.12:1 to 20:1; it can be understood that the mass ratio between the titanium-based material and the hard carbon can be any point value between 0.12:1 and 20:1; illustratively, the mass ratio between the titanium-based material and the hard carbon can be 0.12:1, 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 5:1, 10:1, 15:1, 20:1, etc.; in this way, by introducing the titanium-based material, the sodium storage potential of the hard carbon and the composite negative electrode material can be effectively and accurately regulated, and within this mass ratio range, the sodium storage potential of the hard carbon and the composite negative electrode material can be effectively improved. The negative electrode potential is increased, and the rate performance, cycle performance, stability and safety of the negative electrode sheet and the sodium ion battery having the composite negative electrode material are synergistically improved; in some preferred embodiments, the mass ratio between the titanium-based material and the hard carbon is 0.5:1 to 10:1; further, the mass ratio between the titanium-based material and the hard carbon is preferably 0.5:1 to 2:1, which not only effectively improves the sodium storage potential, rate performance and cycle performance of the composite negative electrode material relative to the hard carbon material, but also effectively improves the rate performance and cycle performance of the composite negative electrode material relative to the titanium-based material.
[0027] Specifically, the sodium storage potential of the composite negative electrode material is 0.1V~0.2V; it can be understood that the sodium storage potential of the composite negative electrode material can be any point value between 0.1V~0.2V; illustratively, the sodium storage potential of the composite negative electrode material can be 0.1V, 0.12V, 0.13V, 0.15V, 0.17V, 0.18V, 0.2V, etc.; compared with the simple hard carbon negative electrode, the sodium storage potential of the composite negative electrode material formed by bonding hard carbon and titanium-based materials has been effectively improved, which can effectively avoid the situation in which the metal sodium precipitates to form sodium dendrites during the charge and discharge process and cause the battery to short-circuit, greatly improving the stability and safety of the composite negative electrode material, negative electrode sheet and sodium ion battery, and at the same time is conducive to the joint improvement of rate performance and cycle performance.
[0028] In addition, during the operation of the sodium ion battery, the volume change rate of the composite negative electrode material before and after sodium insertion is less than or equal to 1.2%; it can be understood that the volume change rate of the composite negative electrode material before and after sodium insertion can be any point value less than or equal to 1.2%; illustratively, the volume change rate of the composite negative electrode material before and after sodium insertion can be 1.2%, 1.1%, 1.0%, 0.9%, etc.; in this way, the volume change rate of the composite negative electrode material before and after sodium insertion is small, so that the structural stability of the composite negative electrode material is good, and accordingly, the structural stability of the negative electrode sheet and the sodium ion battery having the composite negative electrode material is also effectively improved, which can greatly improve the stability and safety of the sodium ion battery having the composite negative electrode material during the charge and discharge process.
[0029] On the other hand, the present application also provides a method for preparing a composite negative electrode material, comprising: S1, ball-milling the hard carbon and the titanium-based material to obtain a mixed dry material; S2, heat-treating the mixed dry material and cooling it to obtain the composite negative electrode material.
[0030] The preparation method of the composite negative electrode material is simple in process, the raw materials of hard carbon and titanium-based materials are abundant, low in cost, non-toxic, highly safe, and suitable for large-scale production.
[0031] Specifically, in step S1, that is, during the ball milling mixing process, the ball milling speed is 200 r / min to 1000 r / min, and the ball milling time is 0.5 h to 12 h; it can be understood that the ball milling speed can be any point value between 200 r / min and 1000 r / min, and the ball milling time can be any point value between 0.5 h and 12 h; illustratively, the ball milling speed can be 200 r / min, 300 r / min, 500 r / min, 600 r / min, 750 r / min, 800 r / min, 1000 r / min, etc. ; The ball milling time can be 0.5h, 1h, 1.5h, 2.5h, 5h, 7h, 10h, 12h, etc.; in this way, the titanium-based material and the hard carbon can be mixed evenly, which is beneficial to improve the structural uniformity of the composite negative electrode material, improve the effectiveness and uniformity of the potential enhancement of the composite negative electrode material, and further synergistically improve the stability, safety, rate performance and cycle performance of the composite negative electrode material, negative electrode sheet and sodium ion battery; in some preferred embodiments, during the ball milling mixing process, the ball milling speed is 300r / min~500r / min, and the ball milling time is 1h~3h.
[0032] Specifically, in step S2, that is, during the heat treatment, the temperature is 300°C to 500°C, the time is 2h to 8h, and the heating rate is 1°C / min to 5°C / min; it can be understood that the heat treatment temperature can be any value between 300°C and 500°C, the time can be any value between 2h to 8h, and the heating rate can be any value between 1°C / min and 5°C / min; illustratively, the heat treatment temperature can be 300°C, 320°C, 350°C, 375°C, 400°C, 45 0℃, 500℃, etc.; the heat treatment time can be 2h, 2.5h, 3h, 4h, 5h, 7h, 8h, etc.; the heating rate during the heat treatment process can be 1℃ / min, 2℃ / min, 2.5℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, etc.; in this way, the microscopic bonding between the evenly mixed titanium-based material and the hard carbon can be promoted, and the bonding tightness between the titanium-based material and the hard carbon in the prepared composite negative electrode material can be improved, which is further beneficial to the improvement of the sodium storage potential of the composite negative electrode material.
[0033] Specifically, the atmosphere of the heat treatment includes at least one of argon, nitrogen, hydrogen and air; illustratively, the atmosphere of the heat treatment can be argon, nitrogen, argon-hydrogen mixture, nitrogen-argon mixture, air, etc.; in this atmosphere, the titanium-based material and the hard carbon can be stably and effectively bonded, thereby improving the bonding tightness between the two, with high preparation accuracy, good preparation reliability and high preparation yield, which is beneficial to further improve the sodium storage potential of the composite negative electrode material.
[0034] On the other hand, the present application also provides a negative electrode sheet, including the composite negative electrode material as described above, or including the composite negative electrode material prepared by the preparation method of the composite negative electrode material as described above, which can effectively improve the negative electrode potential, prevent the precipitation of sodium metal during charging and discharging and cause short circuit, and has high safety in use.
[0035] On the other hand, the present application also provides a sodium ion battery, comprising the composite negative electrode material as described above, or comprising a composite negative electrode material prepared by the preparation method of the composite negative electrode material as described above, or comprising the negative electrode sheet as described above, the sodium ion battery also comprising a positive electrode material and a diaphragm, the diaphragm being located between the positive electrode material and the composite negative electrode material, the composite negative electrode material being able to effectively increase the negative electrode potential, preventing the occurrence of a short circuit caused by the precipitation of sodium metal during the charging and discharging process of the sodium ion battery, and having high safety in use.
[0036] The following describes the embodiments of the present application in combination with the above technical solutions.
[0037] Example 1 The composite negative electrode material of this embodiment is prepared by the following steps: 1. Place the titanium-based material and hard carbon in a ball mill at a mass ratio of 1:1, and mix them by ball milling at a speed of 300 r / min for 1 hour to obtain a mixed dry material; wherein the titanium-based material is an embedded oxide material sodium titanate, and the chemical formula is Na2Ti3O7.
[0038] 2. Place the mixed dry material in a tubular furnace, raise the temperature to 400°C at a rate of 2°C / min in an argon atmosphere, heat treat the mixed dry material for 2 hours, cool it to room temperature and take it out to obtain a composite negative electrode material.
[0039] Example 2 The difference between this embodiment and embodiment 1 is that the mass ratio of sodium titanate to hard carbon is 3:7, that is, HC:NTO=7:3; the rest is the same as embodiment 1.
[0040] Example 3 The difference between this embodiment and embodiment 1 is that the mass ratio of sodium titanate to hard carbon is 7:3, that is, HC:NTO=3:7; the rest is the same as embodiment 1.
[0041] Example 4 The difference between this embodiment and embodiment 1 is that the mass ratio between sodium titanate and hard carbon is 2:1; the rest is the same as embodiment 1.
[0042] Example 5 The difference between this embodiment and embodiment 1 is that the mass ratio between sodium titanate and hard carbon is 1:2; the rest is the same as embodiment 1.
[0043] Example 6 The difference between this embodiment and embodiment 1 is that the titanium-based material is Na2Ti2O5; the rest is the same as embodiment 1.
[0044] Example 7 The difference between this embodiment and embodiment 1 is that during the ball milling mixing process, the ball milling speed is 400 r / min, the ball milling time is 2 h, and during the heat treatment process, the temperature is 500° C. and the time is 3 h; the rest is the same as embodiment 1.
[0045] Example 8 The difference between this embodiment and embodiment 1 is that the titanium-based material is Na2Ti2O5, during the ball milling mixing process, the ball milling speed is 400r / min, the ball milling time is 2h, and during the heat treatment process, the temperature is 500℃ and the time is 3h; the rest is the same as embodiment 1.
[0046] Example 9 The difference between this embodiment and embodiment 1 is that the titanium-based material is titanium dioxide (TiO2); the rest is the same as embodiment 1.
[0047] Comparative Example 1 The difference between this comparative example and Example 1 is that a single hard carbon material is used as the negative electrode material.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that a single sodium titanate (Na2Ti3O7) is used as the negative electrode material.
[0049] Comparative Example 3 The difference between this comparative example and Example 1 is that no heat treatment and cooling are performed, and the specific preparation steps are as follows: Na2Ti3O7 and hard carbon were placed in a ball mill at a mass ratio of 1:1, and ball milled and mixed at a speed of 300 r / min for 1 h to obtain a negative electrode material.
[0050] Comparative Example 4 The difference between this comparative example and Example 1 is that the mass ratio between sodium titanate and hard carbon is 1:9, that is, HC:NTO=9:1; the rest is the same as Example 1.
[0051] The performance of the composite negative electrode material in the above embodiment and the negative electrode material in the comparative example were tested. The test results are shown in Tables 1 and Figure 1-4 shown.
[0052] Table 1 Performance test results of composite negative electrode materials of embodiments and comparative examples
[0053] Among them, Figure 1 and Figure 2 As shown, and according to the performance test results of Examples 1-9, it can be seen that when the mass ratio of hard carbon (HC) and sodium titanate (NTO) is different, or when the titanium-based materials are different, the sodium storage potential of the hard carbon material can be improved to varying degrees, so that the composite negative electrode material has a relatively high sodium storage potential relative to the hard carbon negative electrode, effectively avoiding the precipitation of metallic sodium during the charge and discharge process to produce sodium dendrites, and greatly improving the stability and safety of the sodium ion battery.
[0054] And as Figure 3 and Figure 4 As shown, compared with the negative electrode materials in Comparative Examples 1-2, the rate performance and cycle performance of the composite negative electrode material provided in the embodiments of the present application have also been improved to a certain extent, especially when the mass ratio between hard carbon and sodium titanate reaches 1:1, compared with the simple hard carbon negative electrode and the simple sodium titanate negative electrode, the rate performance and cycle performance of the composite negative electrode material have been significantly improved; that is, when the mass ratio between hard carbon and sodium titanate reaches 1:1, the sodium storage potential, rate performance and cycle performance of the composite negative electrode material are simultaneously significantly improved.
[0055] In addition, in Comparative Example 3, although the sodium storage potential of the simply mixed negative electrode material is improved, the hard carbon and sodium titanate are not tightly combined, resulting in relatively poor rate performance and cycle stability, and the synergistic improvement of the three cannot be achieved. In Example 1, under the same other conditions, the mixed hard carbon and sodium titanate are heat treated, so that the reversible specific capacity can reach up to 137 mAh g -1 , and the capacity retention rate reached a maximum of 71.4%, and the reversible specific capacity and capacity retention rate were greatly improved compared with those in Comparative Example 3; while in Comparative Example 4, the mass ratio of hard carbon and sodium titanate exceeded the range of 0.12:1 to 20:1, the improvement of the sodium storage potential was negligible, and the reversible capacity ratio and capacity retention rate were also low; it can be seen that, relative to a single hard carbon negative electrode, the composite negative electrode material provided in the embodiment of the present application can effectively improve the negative electrode sodium storage potential, improve the stability during the charge and discharge process, and improve the safety during the charge and discharge process; at the same time, compared with a single hard carbon negative electrode and a single sodium titanate negative electrode, the composite negative electrode material provided in the embodiment of the present application can synergistically improve the rate performance and cycle performance, and improve the electrochemical performance, life and safety of the negative electrode sheet and the sodium ion battery.
[0056] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0057] What is described above are only some embodiments of the present application and are not intended to limit the present application. Those skilled in the art should understand that the present application may undergo various changes and improvements, and any modifications, equivalent substitutions and improvements made in accordance with the present application shall fall within the scope of protection required by the present application.
Claims
1. A composite negative electrode material, characterized in that: The composite negative electrode material comprises hard carbon and a titanium-based material, wherein the hard carbon and the titanium-based material are bonded, and the composite negative electrode material is obtained by ball milling, mixing, heat treating and cooling the hard carbon and the titanium-based material.
2. The composite negative electrode material according to claim 1, characterized in that: The titanium-based materials include TiO2, NaTiO2, Na2Ti2O5, Na2Ti3O7, Na4Ti5O 12 、Na2Ti6O 13 At least one of .
3. The composite negative electrode material according to claim 1, characterized in that: The mass ratio between the titanium-based material and the hard carbon is 0.12:1 to 20:
1.
4. The composite negative electrode material according to claim 1, characterized in that: The sodium storage potential of the titanium-based material is 0.25V to 0.35V.
5. The composite negative electrode material according to claim 1, characterized in that: The sodium storage potential of the composite negative electrode material is 0.1V to 0.2V.
6. A method for preparing a composite negative electrode material, characterized in that: include: The hard carbon and the titanium-based material are ball-milled and mixed to obtain a mixed dry material; The mixed dry material is heat treated and cooled to obtain the composite negative electrode material.
7. The method for preparing a composite negative electrode material according to claim 6, characterized in that: During the ball milling mixing process, the ball milling speed is 200 r / min to 1000 r / min, and the ball milling time is 0.5 h to 12 h.
8. The method for preparing a composite negative electrode material according to claim 6, characterized in that: The heat treatment satisfies at least one of the following characteristics: During the heat treatment, the temperature is 300°C to 500°C, the time is 2h to 8h, and the heating rate is 1°C / min to 5°C / min; The atmosphere of the heat treatment includes at least one of argon, nitrogen, hydrogen and air.
9. A negative electrode sheet, characterized in that: The invention comprises the composite negative electrode material as claimed in any one of claims 1 to 5, or comprises the composite negative electrode material obtained by the preparation method of the composite negative electrode material as claimed in any one of claims 6 to 8.
10. A sodium ion battery, characterized in that: It comprises the composite negative electrode material as described in any one of claims 1 to 5, or comprises the composite negative electrode material obtained by the preparation method of the composite negative electrode material as described in any one of claims 6 to 8, or comprises the negative electrode sheet as described in claim 9.